2023
DOI: 10.3390/en16134837
|View full text |Cite
|
Sign up to set email alerts
|

The Necessity and Feasibility of Hydrogen Storage for Large-Scale, Long-Term Energy Storage in the New Power System in China

Abstract: In the process of building a new power system with new energy sources as the mainstay, wind power and photovoltaic energy enter the multiplication stage with randomness and uncertainty, and the foundation and support role of large-scale long-time energy storage is highlighted. Considering the advantages of hydrogen energy storage in large-scale, cross-seasonal and cross-regional aspects, the necessity, feasibility and economy of hydrogen energy participation in long-time energy storage under the new power syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In the design process, the heat transfer fluid velocity lies in the range of 1~2.5 m/s [11]. The total thermal resistance includes the thermal resistance of the hydrogen storage alloy, the thermal resistance of the tube wall, and that for convective heat transfer.…”
Section: Determining Heat Transfer Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In the design process, the heat transfer fluid velocity lies in the range of 1~2.5 m/s [11]. The total thermal resistance includes the thermal resistance of the hydrogen storage alloy, the thermal resistance of the tube wall, and that for convective heat transfer.…”
Section: Determining Heat Transfer Parametersmentioning
confidence: 99%
“…Common techniques for this purpose include solid-state hydrogen storage, low-temperature liquid hydrogen storage, and high-pressure gaseous hydrogen storage. High-pressure gaseous hydrogen storage and low-temperature liquid hydrogen storage are difficult to apply on a large scale due to the constraints of high cost and low safety [9][10][11][12][13][14]. On the other hand, solid-state hydrogen storage using metal hydrides has the advantages of high energy density, small volume, and safe and stable compounds generated, and is thought of as one of the promising technologies of the future.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the FR capacity replaces the standby capacity for the FR, and standby prices are equal [19]. Equations ( 6)- (10) represent the thermal unit output, upper and lower FR, and up and down reserve capacity plan constraints. The climbing constraints for the thermal units are represented by Equations ( 11) and (12).…”
Section: Multitype User Demand Decision-making Based On the Nash Gamementioning
confidence: 99%
“…Ref. [10] explored the role of a long-term ESS in supporting the reliable operation of an RES and compared the operational characteristics of multiple ESSs. The necessity, feasibility, and economics of an HSS participating in the long-term scale under the operation of the RES have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…By shifting one's attention to the big international picture, one can observe that the increasing penetration of wind farms and photovoltaic parks in modern electricity grids results in stochastic electricity production with frequent peaks, which disturb the grid's operation and result in the dumping of large amounts of renewable energy. In an extensive study on the new power system paradigm of China, Yan et al [10] conducted power supply and demand production simulations based on the characteristics of new energy generation in China. They found that when the penetration of new energy sources in the system exceeds 45%, long-term energy storage becomes an essential regulation tool.…”
Section: Introductionmentioning
confidence: 99%